2016
DOI: 10.1123/mc.2014-0072
|View full text |Cite
|
Sign up to set email alerts
|

Postural Steadiness and Ankle Force Variability in Peripheral Neuropathy

Abstract: Introduction The purpose was to determine the effect of peripheral neuropathy (PN) on motor output variability for ankle muscles of older adults, and the relation between ankle motor variability and postural stability in PN patients. Methods Older adults with (O-PN) and without PN (O), and young adults (Y) underwent assessment of standing postural stability and ankle muscle force steadiness. Results O-PN displayed impaired ankle muscle force control and postural stability compared with O and Y groups. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…These findings agree with our similarly-designed studies in larger muscle groups such as the elbow flexors, knee extensors, ankle dorsiflexors, and ankle plantarflexors (Tracy et al, 2007 ; Welsh et al, 2007 ; Paxton et al, 2015 ). For example, in a study of the knee extensors that produced results very similar to the present work (Tracy et al, 2007 ), we showed that the normalized amplitude of force fluctuations during low force isometric contractions was 38% greater for older adults only when high gain visual force feedback was provided, compared with no visual feedback.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings agree with our similarly-designed studies in larger muscle groups such as the elbow flexors, knee extensors, ankle dorsiflexors, and ankle plantarflexors (Tracy et al, 2007 ; Welsh et al, 2007 ; Paxton et al, 2015 ). For example, in a study of the knee extensors that produced results very similar to the present work (Tracy et al, 2007 ), we showed that the normalized amplitude of force fluctuations during low force isometric contractions was 38% greater for older adults only when high gain visual force feedback was provided, compared with no visual feedback.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in our other study of the knee extensors in a similarly-aged subject sample, there was a 38% increase in the CV of force for older adults but no change for young adults during visual feedback compared with no visual feedback (Welsh et al, 2007 ). Also, in our recent study of dorsiflexors and plantarflexors of healthy older adults (mean age 73 years) and older peripheral neuropathy patients (mean age 75 years), we observed significant 1.3-fold to 2-fold increases in the CV of force during low-force isometric contractions when high gain visual feedback was provided (Paxton et al, 2015 ). The changes in young adults (mean age 23 years) were not significant for the dorsiflexors (11% increase, p = 0.22) or relatively small for plantarflexors (28% increase, p = 0.05).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Significant correlations of lower extremity muscle strength to postural stability were detected in both groups, which is consistent with some previous studies ( 7 , 10 ) and inconsistent with another one ( 38 ), in which there was no correlation of ankle strength to postural stability was detected. However, only static postural stability was tested in their study, and postural control included static balance and dynamic balance ( 9 ).…”
Section: Discussionsupporting
confidence: 85%
“…No or minimal age-related difference was observed for tasks performed in the absence of visual feedback. However, the age-related and vision-dependent increased force variability was mainly reported for large muscle groups (Tracy, 2007 ; Tracy et al, 2007 ; Welsh et al, 2007 ; Paxton et al, 2015 ). Here, Tracy et al showed age-related increase in force variability under high-gain visual feedback for an intrinsic muscle of the hand.…”
mentioning
confidence: 99%